MacSween's pathology of the liver - Burt, Alastair D; Portmann, Bernard; Ferrell, Linda D (Churchill Livingstone / Elsevier, 2007)
Highly Commended, Gastroenterology, BMA Awards 2007This lavishly illustrated text provides you with all of the information necessary to effectively diagnose and confidently sign out hepatobilary tissue samples. An invaluable aid to pathologists at all levels of training and practice, this book covers the full range of both benign and malignant lesions of the liver and biliary tract. All entities are accompanied by carefully chosen photographs of outstanding quality. Summary tables, diagnostic flow charts, and analytic tables give you all the information you need for rapid interpretation and accurate diagnosis.Provides you with a complete visual guide to each tumor or tumor-like lesion and assists in the recognition and diagnosis of any tissue sample under the microscope.Gives you a single, functional \"one-stop\" resource for use either in the reporting room or for formal study.Incorporates all of the necessary diagnostic tools to make a complete and accurate pathologic report.Uses tables to simplify and clarify complex concepts and facilitates \"at a glance\" comparisons between entities.Enables quick and easy reference with a consistent, user-friendly format.Improves and expands coverage of increasingly important areas such as FNA biopsy, drug induced liver disease, hepatitis C, and non-alcoholic fatty liver disease (NAFLD).Provides additional coverage of key diagnostic criteria and differential diagnoses for each entity.Adds interventional radiological images where appropriate.
Keywords: patologie; Liver; nemoci jater; játra; Liver Diseases